Patient-Centered Health Education Intervention to Empower Preventive Diabetic Foot Self-care. (July 2020) - Makiling, Meryl; Smart, Hiske
ABSTRACT: BACKGROUND: Diabetes impairs the body's ability to produce or respond to the hormone insulin resulting in abnormal metabolism of carbohydrates and elevated glucose levels in the body. Because of these factors, diabetes can cause several complications that include heart disease, stroke, hypertension, eye complications, kidney disease, skin complications, vascular disease, nerve damage, and foot problems. Diabetes education allows patients to explore effective interventions into living their life with diabetes and incorporate the necessary changes to improve their lifestyle. OBJECTIVE: To educate patients diagnosed with diabetes or followed up for diabetes management by other departments with regard to their own responsibility in maintaining preventive foot self-care. METHODS: Ten patients completed a validated educational foot care knowledge assessment pretest to determine their existing knowledge about their own foot care after a thorough foot assessment. Preventive diabetic foot self-care education was conducted through a lecture, visual aids, and a return demonstration. Patients then took a posttest questionnaire with the same content as the pretest to determine their uptake of the educational content. RESULTS: Correct toenail cutting was the most identified educational need. It was a limitation in the pretest (30%), and it remained the lowest-scoring item on the posttest (70%). Walking barefoot was thought to be safe by 60% of participants pretest, but with remedial education, all participants identified this as a dangerous activity posttest. Participants also understood the high importance of having corns and calluses looked after by a health professional. CONCLUSIONS: Effective communication with patients by healthcare providers who can mold educational content to identified patient needs by teaching much needed skills is a key driver in rendering safe, quality healthcare education interventions.